Selling technology to your CEO - Robb, Walter L.
Walter L. Robb advises technical executives to establish credibility through their excellent performance, teamwork and courage.
Here's advise for defending the long-term R&D effort in an increasingly short-term world.
In an era of severe global competition, slowing growth and short-term expectations, chief executives tend to favor those business functions that can show measurable impact on the bottom line. In this environment, the chief technical officer must defend technology against zealous proposals from the other business functions, in order to preserve the long-term growth and profitability of the business. This role for the CTO requires establishing a high degree of credibility, gained by excellent performance coupled with teamwork, plus the willingness and courage to take the right degree of risk.